BETTER LATE THAN NEVER: IDENTIFICATION OF CHILDREN WITH HEARING LOSS IN PAKISTAN: Children With Hearing Loss in Pakistan - Mumtaz, Nazia; Habibullah, Shaista (Pakistan Armed Forces Medical Journal, 2017)
Objectives: To ascertain the prevalence of late detection of hearing impairment (HI) among the children of Pakistan. It aimed at identification of children with hearing loss.Study Design: Cross sectional survey.Place and Duration of Study: The study was conducted at special schools in three major cities of Pakistan Rawalpindi, Islamabad and Lahore. Duration of study was six months i.e. from March to August 2016.Patients and Methods: A convenient sampling technique was adopted by collecting information through a questionnaire with 125 parents of children with impaired hearting. Children diagnosed with only HI and with no other disability were selected for the study and assessed with questionnaires filled by their parents.Results: The results revealed that late detection of HI was more manifested in the age bracket of 19-24 months at 48% followed by 22% at 0-6 months. The results showed that HI was noticed in 33% cases during 0-6 months age but first professional advise was sought in the age bracket of 19-24 months in 35% cases.Conclusions: The current study has established the prevalence of late detection of HI in Pakistan, as there is a significant time lag between HI being noticed and its final detection.